PENDEKATAN INTERVENSI MULTISEKTOR DALAM PENCEGAHAN STUNTING: TINJAUAN LITERATUR TERBARU 2019–2024 - Maryana, Nana (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Stunting remains a major public health issue in Indonesia, with long-term consequences on physical growth, brain development, immunity, and future productivity. This study aims to review effective multisectoral interventions for stunting prevention based on recent literature published between 2019 and 2024. A literature review method was employed, analyzing 25 relevant national and international journal articles obtained from databases such as Google Scholar, PubMed, and ScienceDirect. The findings reveal that stunting is caused by multiple factors, including inadequate maternal and child nutrition, recurrent infections, poor sanitation, low maternal education, and limited access to health services. Effective interventions include the provision of supplementary feeding, micronutrient supplementation, exclusive breastfeeding promotion, nutrition education, and improvement of sanitation and clean water access. The success of stunting prevention programs significantly depends on multisectoral approaches involving health, education, social welfare, economic empowerment, and food security sectors. Active involvement of families, health cadres, and communities plays a crucial role in ensuring program sustainability. Therefore, strengthening local capacity, integrating nutrition programs with household economic empowerment, and conducting regular evaluations are recommended to adapt strategies to local needs and improve the effectiveness of stunting prevention efforts in Indonesia.. Keywords : Stunting, intervention, pregnant women, under-five children, multisectoral, literature review